The impact of e-GP system in Dhaka WASA : a case study for selected offices - Khan, Mohammad Sohel (BRAC University, 2018)
This dissertation is submitted in partial fulfilment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.